2008
DOI: 10.1158/0008-5472.can-07-5704
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Tumor Necrosis Factor Therapy Inhibits Pancreatic Tumor Growth and Metastasis

Abstract: Chronic inflammation has been implicated in the pathogenesis of many severe autoimmune disorders, as well as in diabetes, pulmonary diseases, and cancer. Inflammation accompanies most solid cancers including pancreatic ductal adenocarcinoma (PDAC), one of the most fatal cancers with surgery being the only curative therapeutic approach currently available. In the present work, we investigated the role of the major proinflammatory cytokine tumor necrosis factor A (TNFA) in the malignancy of PDAC cells in vitro a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
208
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(219 citation statements)
references
References 43 publications
5
208
1
1
Order By: Relevance
“…TNF-a may promote cancer transformation, proliferation, angiogenesis, invasion, and metastasis (5). Animal models provide evidence that TNF-a enhances growth and spread of syngeneic, xenogeneic, and carcinogen-induced tumors of the skin, ovary, and pancreas (28)(29)(30). TNF-a and TNF-a receptordeficient mice have reduced susceptibility to chemically induced skin cancers and develop fewer experimental metastases (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a may promote cancer transformation, proliferation, angiogenesis, invasion, and metastasis (5). Animal models provide evidence that TNF-a enhances growth and spread of syngeneic, xenogeneic, and carcinogen-induced tumors of the skin, ovary, and pancreas (28)(29)(30). TNF-a and TNF-a receptordeficient mice have reduced susceptibility to chemically induced skin cancers and develop fewer experimental metastases (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TNF-a 2/2 mice were unexpectedly resistant to skin carcinogenesis (4), and TNF-a in the tumor microenvironment promotes tumor survival, proliferation, invasion, metastasis, and angiogenesis (5). Additionally, TNF blockade reduced tumor growth as well as decreased colonic infiltration of macrophages and neutrophils in mice (6), and neutralization of TNF-a with specific Ab suppressed the hepatic metastases and prolonged survival (7,8).…”
mentioning
confidence: 99%
“…TNF-α has a pluripotent role in oncogenesis. Supportive care for some cancers, but not AML so far, includes inhibition of TNF signalling through the use of soluble receptors and neutralizing antibodies 18,19 . In vitro experiments published so far demonstrate that cytokines and adhesion molecules form a unique interacting functional network.…”
Section: Discussionmentioning
confidence: 99%